Apoptotic cell-derived extracellular vesicles-MTA1 confer radioresistance in cervical cancer by inducing cellular dormancy - Yuan-Run Deng; Qiao-Zhi Wu; Wan Zhang; Hui-Ping Jiang; Cai-Qiu Xu; Shao-Cheng Chen; Jing Fan; Sui-Qun Guo; Xiao-Jing Chen (Journal of Translational Medicine)
Abstract Background Radioresistance presents a major challenge in the treatment of cervical cancer (CC). Apoptotic tumor cells can create an “onco-regenerative niche,” contributing to radioresistance. However, the intercellular signaling mechanisms mediating the transfer of radioresistance from apoptotic to surviving cancer cells remain unclear. Methods The role of apoptotic tumor cell-derived extracellular vesicles (apoEVs) in mediating radioresistance was investigated through integrated bioinformatics and experimental approaches. The GSE236738 dataset was analyzed to identify potential regulators, with subsequent validation of apoEV-MTA1 function using in vitro and in vivo models. Mechanistic studies focused on caspase-3 activation, p-STAT1 signaling pathway, and dormancy-associated protein networks. Furthermore, therapeutic strategies targeting MTA1 and its downstream signaling were evaluated for radiosensitization potential. Results MTA1 was identified as a critical factor enriched in and transferred by apoEVs from apoptotic tumor cells to neighboring CC cells. Caspase-3 activation facilitated the nuclear export and encapsulation of MTA1 in apoEVs. Transferred MTA1 retained transcriptional activity, activated the p-STAT1 signaling pathway, and induced cellular dormancy via NR2F1, a key dormancy regulator, resulting in increased radioresistance. Knockdown of MTA1 in apoEVs or inhibition of p-STAT1 in recipient cells enhanced radiosensitivity. Furthermore, apoEV-MTA1 promoted tumor radioresistance and reduced survival rates in irradiated cervical cancer mouse model. Conclusions This study demonstrates that apoEV-MTA1 confers radioresistance in CC by promoting cellular dormancy via the p-STAT1/NR2F1 signaling axis. Targeting this pathway could improve radiosensitivity and provide a promising therapeutic strategy for CC patients. Graphic Abstract